(untitled) (Colombia Medica, 2006)
Interest for preventive therapies and nutritional supplementation has increased over the last years. Probiotics are live organisms that once ingested, improve the intestinal balance. The organisms with best experience and information are acid lactic bacteria, mainly Lactobacillus spp y Bifidobacterium spp., which are considered safe for humans. Probiotics beneficial effects have been demonstrated in the fallowing situations: prevention of rotavirus diarrhea in children, diarrhea related to antibiotics use, traveler’s diarrhea, vaginosis, urinary tract infections, food allergies, lactose intolerance and atopic dermatitis. Promising results using proibiotics have been reported in bowel inflammatory disease, necrotizing enterocolitis and irritable bowel syndrome. Recently some evidence suggests that probióticos can improved treatment for Helicobacter pylori and prevent the carcinogenesis process, but more studies are needed in this area. The use of lactic bacteria in the elaboration of vaccines to improve protective effect is under investigation. Although probiotics represent an important therapeutic option more studies are necessary in some areas to elucidate their utility, mechanism of action and determine why and when they fail in different clinical situations.